The Impact of Effective Credit Risk Management Systems on the Survival of Microfinance Institutions - Ruth Endam Mbah (Current Topics on Business, Economics and Finance Vol. 6, 2023)
This book chapter aims to build on existing research to examine the impact that an effective and efficient credit risk management system has on the survival of microfinance. Like any other financial institution, microfinance institutions encounter various forms of risks but their intensity is due to their small sizes and their volume of operations. Of all the risks a financial institution could face, credit risk is one of the most severe. A cluster sampling approach was employed in this study consisting of 200 credit clients and 80 employees of a major leading microfinance institution in Cameroon. Primary data was collected through the use of a designed questionnaire, interview, and personal observation. Results show that there were a good number of lapses in the credit risk management system as highly unmonitored provisions, a poor recovery procedure, credit officers without an educational background in the field, manual execution of some loans, slow credit management processes, the bad faith of customers, and poor follow-up of loans given out. It is vital to note that the survival of every Financial Institution lies in how it can effectively and efficiently manage its loan portfolio. It is thus, of critical importance for every financial institution to have an adequate and efficient credit policy manual, credit process, competent credit personnel, tight loan recovery procedure, and tight control system for its provisions if it must survive in this highly competitive sector having clients who are ready to take advantage of any loopholes.